Digital reference services - Chowdhury, G. G. (Gobinda G.) (Library review, 2004)
It has become increasingly common for libraries to provide a reference service which operates via e-mail or through online forms. This paper compares the performance of three digital reference services available on the World Wide Web, namely, AllExperts, Ask a Librarian, and Internet Public Library (a fourth service, Ask Bob, was included initially but eventually excluded). The online digital reference/''expert'' services are generally very effective; most provide an answer within three days, and include suggestions for sources of further information. Although the general response rate from al.